O Fundef no Rio Grande do Sul - apontamentos de uma pesquisa de acompanhamento e avaliação - Vera Maria Vidal Peroni; Nalú Farenzena (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The text presents results of a research on observation and assessment of the impact of FUNDEF in Rio Grande do Sul, from 1996 to 2000. The description encompasses peculiarities of the constitutional ordination of the State related to the competence and collaborations of the government spheres, teacher's initial studies data and the educational offer during the primary education, the redistribution of resources of FUNDEF in the State, the most meaningful aspects of the impact of the Fund within a 4-year-study research case. The results show the predominance of the public teaching net in the primary education and the distinct growth of the municipal teaching net within the period. The case studies bring out the limited achievement of the conception redistribution of FUNDEF.